Optical modulator based on coupled photonic crystal cavities. Issue 13 (19th July 2016) - Serafimovich, Pavel G.; Kazanskiy, Nikolay L.
Abstract: We propose and numerically investigate an optical signal modulator based on two-photonic crystal nanobeam cavities coupled through a waveguide. The suggested modulator shifts the resonant frequency over a scalable range. We design a compact optical modulator based on photonic crystal nanobeams cavities that exhibits high stability to manufacturing. Photonic crystal waveguide tuning in the low-intensity region of the resonant mode is demonstrated. The advantages of the suggested approach over the single-resonator optical modulator approaches include the possibilities to shift the modulator frequency over a scalable range that depends on switching energy level and to effectively electrically tune the device in the low-intensity region of the resonant mode.